Evaluación de la efectividad de dos herbicidas post-emergentes para el control de malezas en el cultivo de soya (Glycine Max), cultivada en sistema de siembra directa. - López Villalta, Hermes Jacinto (2016)
The research of evaluation of the effectiveness of post-emergent herbicides Quizalofop and Fomesafen to control weeds in soybean (Glycine max) grown in tillage system. This research was conducted between the months of August to December 2014. The property of Mr. Alejandro López, the same that is located on the premises La Ercilia way for Windows. Weeds are generally a problem; decrease the production yield of crops competence of soil nutrients. Weeds are these wide or thin, annual and perennial leaf are a real problem in all agricultural production systems, causing difficulties in handling activities like when fertilizing, irrigation, phytosanitary controls among others including harvesting. The overall objective of the research was to determine the effect of weed control with Quizalofop And Fomesafen growth and crop yield of soybean (Glycine max) in the area of Windows 2014. To achieve the overall objective specific objectives were: To evaluate the growth of soybean cultivation under application of herbicides. Determine the most effective dose of herbicide combinations studied. Analysis of the production costs of the treatments. The experimental design of randomized complete blocks (RCB) was used. The experimental units included 20 parcels of 4m x 4m, corresponding to 5 treatments and 4 replications, the herbicides were mixed Quizalofop 1.5+ 0.75 Fomesafen represented as Treatment 1 Treatment 2 Fomesafen1.0 Quizalofop 2.0+ 1.5+ Quizalofop Fomesafen1.0 tratamineto 3 Quizalofop 2.0+ Fomesafen 0.75 as a treatment 4 and the absolute control without product application handled manually. The results show that the best treatment to No. 2 with greater control than weeds present study and in the best crop yield without causing serious toxicity in culture is achieved since it is not reflected in the performance according to Table given by (European Weed Research Society) to evaluate Weed Control and Phytotoxicity to crops.